Acetylcholine in the hippocampus: problems and achievements - Dobryakova, Yulia V.; Bolshakov, Alexey P.; Korotkova, Tinna; Rozov, Andrey V. (Frontiers in Neural Circuits, 2025)
Cholinergic septohippocampal projections originating from the medial septal area (MSA) play a critical role in regulating attention, memory formation, stress responses, and synaptic plasticity. Cholinergic axons from the MSA extensively innervate all hippocampal regions, providing a structural basis for the simultaneous release of acetylcholine (ACh) across the entire hippocampus. However, this widespread release appears inconsistent with the specific functional roles that ACh is thought to serve during distinct behaviors. A key unresolved question is how the dynamics of ACh tissue concentrations determine its ability to activate different receptor types and coordinate individual synaptic pathways. Here, we highlight several debated issues, including the potential intrinsic source of ACh within the hippocampus – such as cholinergic interneurons – and the co-release of ACh with GABA. Furthermore, we discuss recent findings on in vivo ACh concentration dynamics, which present a new dilemma for understanding ACh signaling in the hippocampus: the contrast between “global” ACh release, driven by synchronous activation of MSA neurons, and “local” release, which may be influenced by yet unidentified factors.